Knowledge and ethics in literature A perspective on literature through the lenses of Karl Ove Knausgård and K.E. Løgstrup - Rabjerg, Bjørn (Res Cogitans, 2018)
This article explores some of the thoughts on literature and its cognitive potential, its revelatory force, found in the philosophy of Danish thinker, philosopher and theologian K.E. Løgstrup. Løgstrup was a professor of ethics and the philosophy of religion at Aarhus University, and he was a very influential person in Danish culture from the 1950’s until his death in 1981. The topic in question here concerns the relation between art and reality – or to put it another way the relation between art and truth. Løgstrup will not be the only stepping stone, however, as we will take our point of departure in contemporary Norwegian novelist, and a philosophical thinker in his own right, Karl Ove Knausgård and the thoughts on literature and art found in his monumental series of six novels, My Struggle.